2009
DOI: 10.1080/13613320903178295
|View full text |Cite
|
Sign up to set email alerts
|

Voices of African‐American doctoral students in special education: addressing the shortage in leadership preparation

Abstract: There is a growing body of literature in examining the experiences of graduate students and faculty of color in education. This paper will provide a review of recent and relevant research on the experiences of graduate students and faculty of color, particularly those attending predominately white institutions (PWIs). Additionally, findings from a recent study of African-American doctoral students in special education will be discussed. Finally, the author will assert the need for future research on the leader… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Wasburn-Moses hypothesized that the differences in satisfaction for African American and Asian students related to the lack of mentorship because students from these groups reported not considering the importance of their adviser or program faculty when selecting a program, whereas students from other racial and ethnic groups prioritized alignment with their interests. Williams Shealey (2009) found a similar trend when interviewing Black special education doctoral students, as they reported feelings of isolation within their program while noting the importance of developing a network of individuals to provide support.…”
Section: Program Climatementioning
confidence: 70%
“…Wasburn-Moses hypothesized that the differences in satisfaction for African American and Asian students related to the lack of mentorship because students from these groups reported not considering the importance of their adviser or program faculty when selecting a program, whereas students from other racial and ethnic groups prioritized alignment with their interests. Williams Shealey (2009) found a similar trend when interviewing Black special education doctoral students, as they reported feelings of isolation within their program while noting the importance of developing a network of individuals to provide support.…”
Section: Program Climatementioning
confidence: 70%
“…Recommendations for ways to improve faculty mentoring of doctoral students were provided by some researchers (Shealey, 2009; Tyler et al, 2012) and included specific suggestions to develop stronger skills in the area of cultural competence, as well as the need for a formal mentoring structure for students of color. In addition, Wasburn-Moses and Therrien (2008) proposed examining ways to mentor students across long distances using technological resources due to concerns about relocation issues.…”
Section: Resultsmentioning
confidence: 99%
“…According to Wasburn-Moses (2008), in a survey conducted about overall satisfaction with their doctoral programs, students indicated that finding work–life balance was their greatest struggle. Through an examination of the experiences of African American special education doctoral students, a participant in Shealey’s (2009) study commented on the need for African American students to build their own network, and that they were supportive to one another in finding balance between work and home. In addition, Dieker et al (2014) shared their doctoral program promoted pushing scholar boundaries as well as an emphasis on finding a balance.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations